The Prevalence of Frascati-Criteria-Based HIV-Associated Neurocognitive Disorder (HAND) in HIV-Infected Adults: A Systematic Review and Meta-Analysis - Wei, Jiaqi; Hou, Jianhua; Su, Bin; Jiang, Taiyi; Guo, Caiping; Wang, Wen; Zhang, Yang; Chang, Biru; Wu, Hao; Zhang, Tong (Frontiers in Neurology, 2020)
Background: The HIV associated mortality is decreasing in most countries due to the widespread use of antiretroviral therapy. However, HIV-associated neurocognitive disorder (HAND) remains a problematic issue that lowers the quality of life and increases the public health burden among people living with HIV. The prevalence of HAND varies across studies and selected samples. Therefore, we aimed to quantitatively summarize the pooled prevalence of Frascati-criteria-based HAND and to explore the potential demographic, clinical, and immunological factors. Methods: A comprehensive literature search in PubMed/Medline, Web of Science, Embase, and PsycINFO was performed. A random-effects meta-analysis was conducted using the event rate (ER) for the estimation of the incidence of HAND. Subgroup meta-analyses were used to evaluate between-group differences in categorical variables. Meta-regression with the unrestricted maximum likelihood (ML) method was used to evaluate associations of continuous variables. Results: Eighteen studies whose sample sizes ranged from 206 to 1555 were included in the final analyses. The estimated prevalence of HAND, ANI, MND and HAD were 44.9% (95% CI 37.4–52.7%), 26.2% (95% CI 20.7–32.7%), 8.5% (95% CI 5.6–12.7%), 2.1% (95% CI 1.2–3.7%), respectively. Factors associated with HAND were percent female, current CD4 count, education level and country development level (all ps < 0.05). Conclusion: Longitudinal cohort and multimodal neuroimaging studies are needed to verify the clinical prognosis and the underlying neurocognitive mechanism of HAND. In addition, it is urgently necessary to establish a standardized HAND diagnostic process.